Correction: design, synthesis and evaluation of cinnamic acid ester derivatives as mushroom tyrosinase inhibitors. Issue 5 (10th May 2018) - Sheng, Zhaojun; Ge, Siyuan; Xu, Ximing; Zhang, Yan; Wu, Panpan; Zhang, Kun; Xu, Xuetao; Li, Chen; Zhao, Denggao; Tang, Xiaowen
Abstract : Correction for 'Design, synthesis and evaluation of cinnamic acid ester derivatives as mushroom tyrosinase inhibitors' by Zhaojun Sheng et al., Med. Chem. Commun., 2018, DOI: ;10.1039/c8md00099a .